Evaluación del efecto de la aplicación de halquinol (halquinox) y manano-oligosacáridos (procreatin) en la alimentación de pollos broilers en la parroquia Angamarca-Cotopaxi - Flores Correa, Marcelo Antonio (2015)
This research was conducted in Angamarca Parish in Pujili canton, Cotopaxi Province. The main objective was to evaluate the effect of mannan-oligosaccharides halkynol in broiler chickens over a period of 42 days. The experiment was conducted in three treatments which 180 animals participated. The first treatment with 60 animals was administrated halkynol 20% at doses of 13, 28 g in 40 kg of food. The second treatment with 60 animals was administrated mannan - oligosaccharides in a dose of 88 g to 40 kg of food. The third treatment was the (witness), with a normal diet based on chicken balanced food. In the experiment the following result was obtained that: Treatment 1 which was with the administration of alkynol to the 20% gave better results in animals that were subjected to the experiment with a weight of 2,300 kg in the final weight....